Tetrahydroxydiboron-Initiated Atom-Transfer Radical Cyclization - Wang, Pengfei; Li, Yuli; Wang, Guangwei (Synthesis, 2021)
In this work, the first diboron reagent initiated atom-transfer radical cyclization was reported, in which the boryl radicals were generated by the homolytic cleavage of a B–B single bond weakened by the coordination of Lewis base. To clarify the role of carbonate and DMF in the cleavage of B–B bond, we calculated the free energy diagram of two pathways by density functional theory (DFT) investigations. The DFT calculation showed that the presence of carbonate facilitates the B–B bond cleavage to form boron radicals, which can be further stabilized by DMF. Subsequent atom-transfer cyclization initiated by stabilized dihydroxyboron radical is also energetically favored.
Keywords: tetrahydroxydiboron; homolytic cleavage; atom-transfer radical cyclization; radical initiator; density functional theory